Tourism in Nepal, Real or Hyperreal: A Postmodern Perspective - Upadhyay, Prakash (NUTA Journal, 2019)
The major argument of this paper is that many countries including Nepal have been active in devising tourism policies to support ideologically driven definitions, cultural heritage and symbols of national identity and ethnicity. However, innovative alterations in the field of tourism, economic, political events and emerging paradigms clarifies that post-modern tourism in Nepal and other countries is facing the challenges of not only about prospects, increasing diversities in tourism types, behaviour, but also about risks, uncertainty and quandaries of emic and etic behaviours. Post-modern tourism has always been associated with mystification, pluralities, prospects, challenges, risks and ostracism. The focus on confusions, risks and uncertainties both real and hyperreal (perceived) associated with behavioural changes, bizarre tourism, perplexity, media roles, political instabilities call for a need to re-conceptualization of culture, tradition and legitimacy and to build up an innovative socio-cultural-political and technological understanding of the issues embedded with post-modern tourism.